Insights into the progressive impact of high-fat-diet induced insulin resistance on skeletal muscle and myocardium: A comprehensive study on C57BL6 mice - Jingxuan Wang; Lizhi Dai; Tong Yu; Jianhua Xiao (PLoS ONE, 2025)
This study aims to provide a theoretical foundation for the future management of diabetes at various stages induced by a high-fat diet. Specifically, it seeks to determine the appropriate pharmacological interventions for each phase of diabetes development and the targeted therapeutic directions at different stages of diabetes progression. This investigation employed C57BL6 mice as experimental subjects, successfully establishing an insulin resistance model through a 12-week high-fat diet. Clinical manifestations, weight, body composition, and overall health of each mouse group were observed on the first day of the 6th, 8th, 10th, and 12th week of high-fat feeding to analyze insulin resistance. Subsequently, open-field test of each mouse group, and histopathological changes in the skeletal muscle and myocardium of each mouse group, along with the detection of protein-level expression of relevant genes, were performed to assess alterations in mitochondrial energy metabolism during insulin resistance. This endeavor aims to contribute insights for future in-depth veterinary research. The outcomes demonstrated that a continuous 12-week high-fat diet successfully induced stable insulin resistance in C57BL6 mice. Following insulin resistance, the motor activity of mice decreased, gradual pathological damage and functional decline were observed in the skeletal muscle and myocardium. The insulin signaling pathway was inhibited, resulting in reduced glucose transport and increased gluconeogenesis. Additionally, mitochondrial dysfunction manifested as diminished ATP synthesis capacity, weakened mitochondrial biogenesis, reduced mitochondrial fusion, increased division, and diminished autophagy. Notably, during insulin resistance progression, skeletal muscles and myocardium in C57BL6 mice predominantly relied on glycolytic pathways for energy supply. In the early stages of insulin resistance, the glycogen synthesis pathway in C57BL6 mouse skeletal muscles was inhibited. Our findings underscore a distinct mechanism in skeletal muscle and myocardium that ensures the utilization of anaerobic fermentation to meet energy demands in instances of inadequate aerobic respiration (Fig 1).